Love walked in : a novel - De los Santos, Marisa, 1966- (New York : Plume, 2006)
Eleven-year-old Clare Hobbes takes her life into her own hands after her mother disappears, and sets out to find her estranged father, befriending Cornelia, a coffee shop waitress struggling to realize her dreams, along the way.
Kirkus Starred.
Library Journal.
Wilson's Fiction.
Adult
Keywords: Custody of children -- Fiction; Fathers and daughters -- Fiction; Motion pictures -- Appreciation -- Fiction; Restaurants -- Fiction; Child custody -- Fiction; Father-daughter relationship -- Fiction; Love stories; Motion pictures -- Fiction; Restaurants -- Fiction; Philadelphia (Pa.) -- Fiction; Philadelphia (Pa.) -- Fiction; Love stories